Learning Supervision And Principal's Work Motivation Towards Teacher Performance At State Vocational High School 2 Tahuna - Rio Metri Abast (Journal on Education, 2025)
This research is motivated by poor supervision of learning and lack of work motivation of the principal as one of the factors causing low teacher performance, thus causing a decline in the quality of education. The purpose of this study is to determine and analyze the effect of supervision of learning (X1) and work motivation of the principal (X2) on teacher performance (Y) of Vocational High School 2 Tahuna. This research was conducted at Vocational High School 2 Tahuna. This type of research uses a quantitative approach, using a descriptive study method, namely a method that is directed at solving problems by presenting or describing the results of the study as they are. The conclusions obtained from this study are: (1) Learning Supervision has a very large influence on Teacher Performance with a correlation index of 0.756. This shows that it is important for every teacher to understand learning supervision in teaching and learning activities at Vocational High School 2 Tahuna. (2) The work motivation of the principal has a positive influence on teaching and learning activities because in this study the correlation index of the principal's work motivation is 0.663. (3) Learning supervision and teacher work motivation have a very large influence on improving teacher performance at Vocational High School 2 Tahuna. This can be proven that through hypothesis testing it can be accepted. Through overall analysis and testing, the calculated F of 37.484 is obtained, which is greater than the F table of 3.30, which means that there is a significant influence between Learning Supervision and Principal's Work Motivation on Teacher Performance at Vocational High School 2 Tahuna, Sangihe Regency.